Stability and optimal control of nonlinear descriptor systems: A survey - Müller, Peter C. (Zielona Góra: Uniwersytet Zielonogórski)
In recent years the analysis and synthesis of control systems in descriptor form have been established. This general description of dynamical systems is important for many applications in mechanics and mechatronics, in electrical and electronic engineering, and in chemical engineering as well.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka